Antipodal Vivaldi antennas with foldable hinged plates for adaptive polarization and gain adjustments. Issue 1 (1st December 2017) - Byun, G.; Lim, T. H.; Kang, M. C.; Choo, H.
Abstract: This letter proposes a novel approach to adaptive polarization and gain adjustments for antipodal Vivaldi antennas using foldable hinged plates. The proposed antenna consists of upper and lower flared wings, and the wings are electrically extended using two rectangular plates. Metal hinges are then adopted to fold and unfold the plates, which allows the antenna to adjust the polarization in the entire range of the axial ratio and to further enhance the gain in the end‐fire direction. Measured antenna characteristics demonstrate that the polarization and the gains are adaptively adjusted by varying the tilt angles of the hinged plates without a distortion of the broadband properties.